(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2015)
Present study deals with the impact of climatic factors (temperature, humidity and wind speed) on agromyzid leafminers infestation in three cultivated crops viz. Tomato, French bean and Cowpea. Correlation studies showed that there was significantly positive relation of temperature, whereas wind speed showed negative relation to agromyzid infestation on cultivated crops. But there was no significant relation with humidity. Temperature influenced infestation rate as 18.70 ± 4.12, 16.01 ± 15.85 and 9.38 ± 9.10 % for Tomato, French bean and Cowpea respectively. Asiat. Soc. Bangladesh, Sci. 41(1): 1-5, June 2015